Clinical Presentation, Management and Outcome of Gestational Trophoblastic Diseases Admitted in Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Gestational Trophoblastic Disease (GTD) is a heterogeneous group of diseases that includes partial and complete hydatidiform mole, invasive mole, choriocarcinoma and placental site trophoblastic tumour. The study aimed to determine the clinical presentation management options and outcome of GTD in patients admitted in a tertiary hospital of Bangladesh.Materials and methods: This prospective observational study included 50 patients with GTD from the Obstetrics and Gynaecology Department of Chittagong Medical College Hospital, during the period of July 2013 to December 2013. The demographic profile, clinical presentation, management, outcome and complications were studied.Results: Mean age was 25.40 ± 8.34 years with most of the patients (46%) were in age group 20 - 29 years. 42% participants were primigravida. The commonest symptom after bleeding per-vaginum (94%) was amenorrhea (90%). Maximum cases (80%) were of complete hydatidiform mole. Rate of progression to invasive mole and choriocarcinoma were found 6% and 10% respectively. Suction evacuation and hysterectomy were the treatment option. One patient (2%) expired due to excessive bleeding.Conclusion: The majority of cases are cured by simple suction uterine curettage. Regular follow up is important to estimate the true incidence of this disease.JCMCTA 2021 ; 32 (2) : 128-131